OPTIMALISASI AKUNTANSI MANAJEMEN DALAM PENGAMBILAN KEPUTUSAN STRATEGIS DI PERUSAHAAN MANUFAKTUR - Febryantahanuji Febryantahanuji; Eka Satria Wibawa; Nindi Anggi Wardani; Hendri Rasminto; Sri Wahyuning (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
This study aims to analyze the role of management accounting in supporting strategic decision making at PT ABC, a manufacturing company. Management accounting is seen as an important tool in providing relevant financial and non-financial information for planning, controlling, and evaluating performance (Langfield-Smith, 2008). The research method used is a case study with a qualitative approach, where data is collected through in-depth interviews with management and accounting staff, as well as analysis of internal company documents. The results of the study indicate that management accounting plays an important role in providing production cost information, profitability analysis, and performance reports, which are the basis for management in making strategic decisions such as determining selling prices, allocating resources, and planning production capacity (Chenhall & Moers, 2015). However, the study also identified several challenges, such as limitations in information systems and data integration between departments. The implication of this study is the need to improve management information systems and staff training to maximize the benefits of management accounting in strategic decision making. These findings are expected to contribute to the development of more effective management accounting practices in manufacturing companies (Hall, 2010).